Early assessment of a rapid alternative method for the estimation of the biomethane potential of sewage sludge. (April 2016) - Bellaton, Solenn; Guérin, Sabrina; Pautremat, Nathalie; Bernier, Jean; Muller, Mathieu; Motellet, Stéphane; Azimi, Sam; Pauss, André; Rocher, Vincent
Highlights: Fast fluorescence-based method to investigate biodegradability of sewage sludge. Proportionality between fluorescence and metabolic activity of anaerobic sludge. Assessment of nineteen municipal sewage sludge by this method and by AMPTS. Similar results between AMPTS and rapid alternative method for BMP measurement. Abstract: This short communication briefly presents a rapid method using a fluorescent redox indicator, similar to resazurin, in order to estimate the biodegradability of sewage sludge during anaerobic digestion (AD). The biodegradability and by extension the Biochemical Methane Potential (BMP) of nineteen municipal sludge samples (primary, biological and tertiary) were investigated and estimated in only 48 h. Results showed the relevance to follow the metabolic activity of anaerobic sludge by the kinetic of probe reduction. The extended lag phase of inoculum indicated an impact of pre-treatments on enzyme activity. The comparison with Automatic Methane Potential Test System II (AMPTS) confirmed the estimated values of BMP according to an uncertainty limit of 25%. These first results highlight the interest of this rapid assay as a preliminary tool of the biodegradability of sewage sludge in anaerobic digestion.